TRENDS IN THE CATCH OF SILVERBELLIES BY MECHANISED BOATS IN TAMIL NADU DURING 1971-75 - Annam, V P; Dharmaraja, S K (Indian Journal of Fisheries, 2011)
Silverbellies form an important demersal fishery of India particularly on the coasts of southern maritime states, the annual average catch amounting to about 3% of the total marine fish CEtoh ia India. In Tamil Nadai, mechanised boats predominantly operate at iRoyapuram (Kasimedai), Cuddflore, Portonovo, Adirampatnarri, Mandapam, Rameswaram and land considerable quantities of silverbellies. The catch trends of silverbellies landed by the mechanised boats in Tamil Nadu during the period 1971 to 1975 and the relation between the index of abundance and the toU’l fishing effort both in respect of total landings and landings of silverbellies are dealt with in the present paper.